Monetarist para politikası yaklaşımı ve Azerbaycan merkez bankasının izlediği para politikası - Aziziov, Mais (My University, 2007)
Monetarist Para Politikası ve Azerbaycan Merkez Bankasının İzlediği Para politikası Para miktarındaki değişliliklerin ekonomi üzerindeki artan etkisiyle para politikalarının önemi yükselmeğe başlamıştır. 1960 yıllarından sonra enflasyonla işsizliğin bir arada yükselmesi sonucu monetarist para yaklaşımı teorileri önemsenmeğe başlanmıştır. Azgelişmiş ülkelerin de başlıca problemleri enflasyon ve işsizlik olduğundan biz tezimizde Monetarist para politikası yaklaşımı ve Azerbaycan Bankasının Uyguladığı Para Politikalarını incelemeğe çalıştık. Tezimizin birinci bölümünde para politikasının amaçları, araçları, etkinliği, para politikasında gecikme sorunu, azgelişmiş ülkelerde para politikası ve Klasik, Keynesyen ve yeni Klasik para politikaları şeklinde incelemeye çalıştık. İkinci bölümde Monetarist yaklaşımın temel önermeleri, Yani Miktar teorisi, para talebi, para arzına değinmeğe çalıştık. Aynı zamanda doğal işsizlik oranı ve uzun dönem Phillips eğrisi, enflasyon, para miktarı ve faiz ilişkileri, emek piyasası, monetarist aktarım mekanizması ve monetarist para politikasının reçetesi şeklinde araştırdık. Son bölümde Azerbaycan Merkez Bankasının izlediği para politikaları ve bunların monetarist para politikası açısından değerlendirilmesi bölümünde bağımsızlık sonrası Azerbaycan ekonomisinin genel değerlendirilmesini yaptık. Bununla birlikte Azerbaycan’da bankacılık sistemi ve Azerbaycan Merkez Bankasının kuruluşu ve yapısını inceledik. Daha sonra Azerbaycan Merkez Bankasının 1994–2006 yıllarında uyguladığı para politikalarını ve bunların sonuçlarını araştırdık. Bu bağlamda enflasyonun, döviz kurunun, faiz politikasının ve para arzının monetarist para politikası açısından değerlendirip ve sonuçta en küçük kareler yöntemine göre regresyon modeli aracılığıyla para arzı ve enflasyon arasında ilişki göstermeye çalıştık.

Monetarist Monetary Policy and Monetary Policy of the National Bank of Azerbaijan The increasing effects of the money quantity variables on economy have attracted the importance of the monetary policy . After the 1960’s, the result of the increasing of inflation with unemployment the approach of the monetary theory has started to gain its importance. Because of the main problems of the least developed countries which are the inflation and unemployment, the monetarist monetary policy approach and the implementation of monetary policy on the national bank at Azerbaijan has been taken for research. In the first section, the aim of the monetary policy, mechanism, the problem of late implementation of monetary policy, the monetary policy in the least developed countries and Classic, Keynesian and neo-Classic monetary policy have been taken for research. In the second section, the core suggession of monetarist approach, in other words, quantity theory, money demand, money supply has been touched upon. At the same time, the rate of the natural unemployment and long term Phillips curve, inflation, money quantity and interest rate relations, labour market, monetarist transfer mechanism and the solution of the monetarist monetary policy has been taken for research. In the final section, the implementation of the monetary policy of the national bank of Azerbaijan and in the light of this, we have made a general evaluation of after the independence of Azerbayjan in terms of monetarist monetary policy. Moreover, we examined the banking system of Azerbaijan and the establishment and structure of the national bank of Azerbaijan. Then, we examined the implementation of monetary policy of the national bank of Azerbaijan between 1994-2006’s and the consequences. In this term, we evaluated inflation, foreign exchange rate, interest rate policy and money supply in terms of monetarist monetary policy and we tried to demonstrate the relationship between money supply and inflation using the least square technique in the regression model.
Keywords: Ekonomi Politikası; Para Politikası_Azerbaycan